2015
DOI: 10.1093/nutrit/nuv005
|View full text |Cite
|
Sign up to set email alerts
|

Dietary modification and supplementation for the treatment of age-related macular degeneration

Abstract: Age-related macular degeneration (AMD) causes a significant proportion of visual loss in the developed world. Currently, little is known about its pathogenesis, and treatment options are limited. Dietary intake is one of the few modifiable risk factors for this condition. The best-validated therapies remain oral antioxidant supplements based on those investigated in the Age-Related Eye Disease Study (AREDS) and the recently completed Age-Related Eye Disease Study 2 (AREDS2). In this review, current dietary gui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
66
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(67 citation statements)
references
References 133 publications
1
66
0
Order By: Relevance
“…There are good rates of compliance with the dietary advice; that is, patients change their diet but patient education by health professionals can be improved [120]. …”
Section: The Genetic Risk Lifestyle and Amdmentioning
confidence: 99%
See 2 more Smart Citations
“…There are good rates of compliance with the dietary advice; that is, patients change their diet but patient education by health professionals can be improved [120]. …”
Section: The Genetic Risk Lifestyle and Amdmentioning
confidence: 99%
“…If the patients are unsure of their dietary lutein intake, they should be advised to use lutein/zeaxanthin AREDS-based supplements, given the lack of side effects found in most trials [120]. If they have a normal or high dietary lutein intake they can consume the modified beta-carotene free AREDS formulation [120].…”
Section: Conclusion: Nutritional Advice To Patients With Amdmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the Age-Related Eye Disease Studies (AREDS) demonstrated that the disease process can be impacted by nutritional interventions 24 . It is important to note that AREDS supplements are useful in slowing the progression of existing disease but do not appear to prevent development of AMD 5 . Moreover, the benefits or safety of using such high-dose antioxidants for long periods, as might be needed in patients with AMD, has not been established 2, 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Animal models and the Age-Related Eye Disease Study (AREDS) trial strongly support a role for oxidative stress in the development of AMD. 4,5 Because of the importance of oxidative stress as a contributing factor in AMD, treatments that reduce the accumulation of reactive oxygen species (ROS) may be valuable as therapeutics, though antioxidant therapy has shown more benefit in preventing progression to wet AMD than to GA. 69 Our lab has developed a mouse model of GA in which the knockdown or deletion of Sod2 , the gene for manganese superoxide dismutase (MnSOD), in the RPE leads to elevated oxidative stress, causing some of the features of GA including damage to the RPE and Bruch's membrane and death of photoreceptors. 10,11 Depletion of MnSOD in the RPE in mice shows accumulation of lipofuscin-like fluorescent aggregates containing A2E and Iso-A2E.…”
mentioning
confidence: 99%